1976
DOI: 10.1002/food.19760200605
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical, Biochemical and Ultrastructural Studies on the Liver of Fasted Rats

Abstract: The subjection of rats with body weight 150 +/- 10 g to complete starvation for a period of four days leads to a diminution of total protein, total lipids, blood sugar, body weight and liver weight. Lipid dystrophy develops in the liver, as well as deposition of lipofuscin-like pigment and atrophy. Lipid dystrophy and desposition of pigment increase during the first three days and abruptly decrease during the fourth. Atrophy is a progressive process. The delineation of three phases in the atrophic - dystrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The activation of autophagy in male rats exposed to ADF was studied by Donati et al They assessed the rate of autophagic proteolysis in isolated rat hepatocytes and found that the rate of autophagy was higher in the fasting group than in the control group at all ages (109). Krustew et al studied the effects of 1-8 days of fasting on the size and number of lysosomes in rat hepatocytes and noted a significant increase in the number of lysosomes, and particularly secondary lysosomes (110). After fasting for 12, 24, 48, and 72 hours, the cytoplasmic volume fraction of autophagic vacuoles in liver cells increased significantly compared to feeding for 3 hours.…”
Section: Hepatic Autophagy Mediated By If: Key Eventsmentioning
confidence: 99%
“…The activation of autophagy in male rats exposed to ADF was studied by Donati et al They assessed the rate of autophagic proteolysis in isolated rat hepatocytes and found that the rate of autophagy was higher in the fasting group than in the control group at all ages (109). Krustew et al studied the effects of 1-8 days of fasting on the size and number of lysosomes in rat hepatocytes and noted a significant increase in the number of lysosomes, and particularly secondary lysosomes (110). After fasting for 12, 24, 48, and 72 hours, the cytoplasmic volume fraction of autophagic vacuoles in liver cells increased significantly compared to feeding for 3 hours.…”
Section: Hepatic Autophagy Mediated By If: Key Eventsmentioning
confidence: 99%
“…Kovacs et al showed that fasting significantly increased the cytoplasmic volume fraction of autophagic vacuoles and of dense bodies, whereas insulin levels steadily decreased during fasting periods, as expected [ 84 ]. Another study showed that the number of lysosomes in rat liver cells significantly increased after 1–8 days of fasting [ 85 ]. The same study also showed a direct link between autophagy induction and starvation [ 85 ].…”
Section: The Link Between Endoplasmic Reticulum (Er) Stress Oxidative...mentioning
confidence: 99%
“…Another study showed that the number of lysosomes in rat liver cells significantly increased after 1–8 days of fasting [ 85 ]. The same study also showed a direct link between autophagy induction and starvation [ 85 ]. When the effect of calorie restriction on mitochondrial autophagy was investigated in mice, it was observed that the number of liver mitochondria was increased as a response to food deprivation, and autophagy was readily induced [ 86 ].…”
Section: The Link Between Endoplasmic Reticulum (Er) Stress Oxidative...mentioning
confidence: 99%
“…Die Postimmunisationshylasie envies sich unter diesen Bedingungen als ,,uneffektiv", da die blastotransformierten Zellen bedeutend reduziert sind. Der Einsatz von eigenen Ressourcen zur Deckung des energetischen Bedarfes und die Zufuhrung von nahrstomialtigen Ingredienzien erfolgt bei der starken EiweiBresttiktion durch die um ein vielfaches verstiirkte autophage Funktion des Lysosomenapparates [6,7,9], die in diesem Fall auch die spezifischen antikorperbildenden Zellen betrifft. Aukrdem berechtigt die festgestellte Anzahl an wahrscheinlich bereits inaktivierten Lysosomenformen (Restkorperchen) in den Milzmakrophagen zu der Annahme, daO sich unter den Bedingungen der starken EiweiDrestriktionsernihrungdieinterlysosomale Verarbeitung des eindringenden Antigens [I, 13-151 nicht verwirklichen konnte.…”
Section: Diskdonunclassified